Pengaruh Layanan Informasi Melalui Media Video Terhadap Pemahaman Bahaya Narkoba Peserta Didik Kelas VIII di SMPN 1 Ciledug - Pijar Hudan Muhammad; Wiwik kusdaryani; Farikha Wahyu Lestari (Journal on Education, 2023)
This research is motivated by several problems, namely: 1) information services using video media have been carried out when using classical guidance, but have not been carried out in a sustainable manner; and 2) students' knowledge of the types of drugs and the resulting impacts of 23% is still in the less category. The purpose of this study was to determine the influence of information services through video media on the understanding of the dangers of drugs for class VIII students at SMPN 1 Ciledug. This study used a quantitative approach with the Pre-Experimental Designs of the One Group Pretest-Posttest Design type. The population in this study were all class VIII students at SMPN 1 Ciledug totaling 266 students. The research sample was students of class VIII B SMPN 1 Ciledug totaling 30 participants. The sampling technique used in this research is purposive sampling. Data collection techniques using test techniques. The data analysis technique used is descriptive statistics. Data prerequisite test uses validity, reliability, normality, and homogeneity. Test the hypothesis using paired samples t-test.The results of the research that has been carried out show that information services using video media to understand the dangers of drugs have been implemented well for students in class VIII B at SMPN 1 Ciledug. The results of the hypothesis test with the paired sample t-test that has been carried out obtained the sig value. 2-tailed is 0.000 <0.05, so there is an influence of information services through video media on the understanding of the dangers of drugs in class VIII students at SMPN 1 Ciledug. The effect of the difference in the average mean pre-test and post-test, that is, obtained an average mean pre-test of 78.53 to an average mean post-test of 88.30, then an increase in the average mean of 9.767 is obtained or 10%. It can be concluded that information services through video media can influence the understanding of the dangers of drugs for class VIII students at SMPN 1 Ciledug.